DYNAMICAL JUMP ATTENUATION IN A NON-IDEAL SYSTEM THROUGH A MAGNETORHEOLOGICAL DAMPER - Piccirillo, Vinicius; Tusset, Angelo Marcelo; Balthazar, Jose Manoel [UNESP] (Polish Soc Theoretical & Applied Mechanics, 2014)
This paper is concerned with the Sommerfeld effect (Jump phenomena) attenuation in an non-ideal mechanical oscillator connected with an unbalanced motor excitation with a limited power supply (non-ideal system) using a magnetorheological damper (MRD). The dynamical response of systems with MRD presents different behavior due to their nonlinear characteristic. MRD nonlinear response is associated with adaptive dissipation related to their hysteretic behavior. The Bouc-Wen mathematical model is used to represent the MRD behavior. Numerical simulations show different aspects about the Sommerfeld effect, illustrating the influence of the different electric current applied in the MRD to control the force developed by this damper.
Keywords: magnetorheological damper; Sommerfeld effect; nonlinear dynamics